2017
DOI: 10.18632/oncotarget.14739
|View full text |Cite
|
Sign up to set email alerts
|

A methodological study of genome-wide DNA methylation analyses using matched archival formalin-fixed paraffin embedded and fresh frozen breast tumors

Abstract: BackgroundDNA from archival formalin-fixed and paraffin embedded (FFPE) tissue is an invaluable resource for genome-wide methylation studies although concerns about poor quality may limit its use. In this study, we compared DNA methylation profiles of breast tumors using DNA from fresh-frozen (FF) tissues and three types of matched FFPE samples.ResultsFor 9/10 patients, correlation and unsupervised clustering analysis revealed that the FF and FFPE samples were consistently correlated with each other and cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…This was not only true for the 6 HGSC tumors but also for the benign and borderline tumors included in our study, indicating that this could be the general case for ovarian tumors despite disease severity. Similar correlations between fresh frozen tissue and FFPE tissue have been recently reported for brain tumors and breast tumors [ 28 , 29 ]. Noteworthy, one report has shown that the EPIC platform performs well in fresh frozen and FFPE tissue.…”
Section: Discussionsupporting
confidence: 81%
“…This was not only true for the 6 HGSC tumors but also for the benign and borderline tumors included in our study, indicating that this could be the general case for ovarian tumors despite disease severity. Similar correlations between fresh frozen tissue and FFPE tissue have been recently reported for brain tumors and breast tumors [ 28 , 29 ]. Noteworthy, one report has shown that the EPIC platform performs well in fresh frozen and FFPE tissue.…”
Section: Discussionsupporting
confidence: 81%
“…Formalin-fixed paraffin embedded (FFPE) samples (punches, curls, or sections) [12] were deparaffinized, lysed, incubated until completely digested, and heated to inactivate the Proteinase K. Following bisulfite treatment, FFPE lysates were restored using the Infinium HD DNA Restoration Kit (Illumina). DNA was purified using the DNA Clean & Concentrator-5 kit (Zymo Research) for quantification by Quant-iT Picogreen (Invitrogen) and block randomized across plates with respect to self-reported race, sample type (slide, punch, or curl), patient age, and ER status using the OSAT program [13].…”
Section: Methodsmentioning
confidence: 99%
“…or differing preparation protocols (e.g. addition of the DNA restoration step for FFPE, ( 46–48 )). Enriched labels also varied by storage condition among low-signal samples (binomial test, BH-adjusted P < 1e-3), where ‘colorectal,’ ‘intestine,’ and ‘mucosa’ were enriched among FFPE, while ‘nasal,’ ‘pancreas,’ and ‘epithelial’ were enriched among FF samples.…”
Section: Resultsmentioning
confidence: 99%